Understanding Loss to Follow-Up in AMD Patients Receiving VEGF Inhibitor Therapy: Associated Factors and Underlying Reasons - Pavol Kusenda; Martin Caprnda; Zuzana Gabrielova; Natalia Kukova; Samuel Pavlovic; Jana Stefanickova (Diagnostics, 2024)
Background: In patients with wet age-related macular degeneration (AMD), loss to follow-up (LTFU) leads to unplanned interruptions in therapy and the risk of visual loss. Methods: This retrospective and prospective case–control cohort study compared AMD patients with (LTFU YES) and without (LTFU NO) LTFU during anti-VEGF treatment over 12 years. LTFU was defined as missing any treatment or monitoring visits, or not scheduling follow-ups for six months. Results: Significant differences between LTFU NO (n = 298) and LTFU YES (n = 174) groups were age, treatment phase, baseline and final best-corrected visual acuity (BCVA), type of anti-VEGF drug, treatment switch, commuting distance, and escort during commuting. A multivariate logistic regression analysis identified the need for an escort during the commuting and treatment phase as the only significant difference. The four most common reasons for LTFU were general health worsening (21.8%), patient-missed appointments (16.7%), COVID-19-related issues (14.9%), and treatment dissatisfaction (8.6%). Conclusions: The factors associated with increased LTFU rates were older age, inactive treatment phase, lower baseline and final BCVA, bevacizumab treatment, monotherapy, longer travelling distance, and commuting with an escort. According to the multivariate logistic regression analysis, only the escort during the commuting and treatment phases was significant. These findings could direct research to explore social support in treatment adherence and highlight the importance of treatment phases in practice.